The many graveyard books: artistic collaborations and possible multiple readings in illustrated works - Renata L. Dalmaso; Thayse Madella (Ilha do Desterro)
This article investigates how diverse layers of meanings can be seen in different iterations of the same work, as it is illustrated or adapted by different artists. Departing from a single source material, Neil Gaiman’s The Graveyard Book (2008), we analyze two versions and one adaptation of the text: one novel illustrated by Dave Mckean (2008) and another by Chris Riddell (2009); and a graphic novel (2014), adapted by P. Craig Russell. We draw our analysis from authors in the fields of Children's Literature and Comics Studies to dicuss the construction of meanings between the interplay of written and visual texts. Such interactions have a range of variation taking into consideration both the format of the work (novel or graphic novel), the choice of a scene to be illustrated, and stylistic approaches.